THE USE OF VARIATION OF SLOW LANGUAGE ON STREET CHILDREN (SOCIOLINGUISTIC STUDY) - Syahraini Nursyifa Camila; Ratna Dewi Kartikasari (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Our communication uses language, but often outside Indonesian language is retarded because of the influence of language, so that the use of language is rarely done in everyday life, especially in this day and age. as the national language is maintained. Indonesian is the language of unity, so as Indonesians who care about and respect their national language, we must protect and share our language, namely Indonesian. If we have used good and correct Indonesian, people around us will be infected directly. The researcher used a qualitative descriptive method with the technique of observing and recording the environment.